Investigation of jolt squeeze machine specifications for dumbell design production and its characterizations / Muhammad Danish Haikal Hamzah - Hamzah, Muhammad Danish Haikal (2024)
This project explores the use of jolt squeeze machines in foundries to produce sand molds and its relevance to dumbbell design production. Jolt squeeze machines are ideal for small-scale and batch production of castings. However, they are not currently utilized in Personal Knowledge Management (PKM) due to the need for students to learn the basics before exploring advanced techniques and this project aims to highlight the machine's capabilities and demonstrate its suitability for use by PKM students. Additionally, this project examines the machine's parameters and their effects on molding sand. By using this machine, the molding sand can be compacted easily and efficiently, resulting in consistent products. The project investigates the machine's significant factors that contribute to the production of dumbbell designs with varying specifications. Ultimately, the project provides valuable insights into the use of jolt squeeze machines for sand mold production and their potentialfor use in PKM.